Antibiotic safety among neonates and paediatrics in a public hospital: KwaZulu-Natal - Tyler A. Frank; Frasia Oosthuizen; Varsha Bangalee (AOSIS, 2023)
Background: The World Health Organization (WHO) guidelines recommend the empiric treatment of infections before definitive treatment begins. However, ethical concerns limit the availability of clinical trials in neonates and paediatrics to fully ascertain the safety profile of antibiotics in these populations. Aim: This study aimed to quantify the use of antibiotics among neonates and paediatrics and commented on the use, rationale and appropriateness of antibiotics prescribed. Setting: A secondary level public sector hospital located in Durban, KwaZulu-Natal. Methods: Demographic and treatment information of neonates and paediatrics were collected retrospectively from January 2022 to June 2022. Data were obtained from patient files and extracted for analysis using Microsoft Excel®. Analytical and descriptive statistics were used to analyse patient demographics and treatment variables. Results: A total of 568 antibiotics, issued to 389 patients, were reviewed. Penicillins (40.1%), aminoglycosides (24.3%) and combination penicillin-beta-lactam inhibitors (23.3%) were identified as the most frequently prescribed antibiotics for inpatients. Most antibiotics prescribed to inpatients were for complications associated with pre-term birth (66.9%). Combination penicillin-beta-lactam inhibitors (34.7%), penicillins (29.5%) and cephalosporins (29.5%) were the most frequently prescribed antibiotics to outpatients. A correlation was found between the route of administration and the duration of therapy; the intravenous route (63.6%) was preferred over the oral route (36.4%) for administration. Conclusion: Many broad-spectrum antibiotics were prescribed, thus increasing the risk of resistance. Antibiotics were being prescribed according to the guidelines; however, there is still a need for therapeutic drug monitoring to ensure the continuation of rational drug use. Contribution: There was evidence of rational use of antibiotics in the public hospital (KwaZulu-Natal), in keeping with economic and availability factors.